2010
DOI: 10.1007/s10681-010-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize

Abstract: High-oil maize (Zea mays L.) has special value in animal feed and human food. Two hundred and eight-four and 265 F 2:3 families developed from two crosses between one high-oil maize inbred and two normal dent maize inbreds were evaluated for grain oil and starch contents under two environments. Using composite interval mapping, 1-6 QTL for each trait were detected under each environment and in combined analysis in both populations. Only one common QTL across two environments in each population and across two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
7
35
0
Order By: Relevance
“…A positive relationship between grain protein and oil content has been reported in studies using Illinois maize strains (Goldman et al, 1993;Lambert, 2001;Wassom et al, 2008), BHO (Zhang et al, 2008), ASK high-oil (Li et al, 2009;Wang et al, 2010), and popcorn germplasms (Liu et al, 2008). Curtis et al (1968) showed that the total germ weight and percentage increased with selection of oil and fatty acid composition in IHO after 65 generations, and the protein content also increased.…”
Section: Comparison Of Qtls Detected For Grain Protein and Oil Contenmentioning
confidence: 89%
See 3 more Smart Citations
“…A positive relationship between grain protein and oil content has been reported in studies using Illinois maize strains (Goldman et al, 1993;Lambert, 2001;Wassom et al, 2008), BHO (Zhang et al, 2008), ASK high-oil (Li et al, 2009;Wang et al, 2010), and popcorn germplasms (Liu et al, 2008). Curtis et al (1968) showed that the total germ weight and percentage increased with selection of oil and fatty acid composition in IHO after 65 generations, and the protein content also increased.…”
Section: Comparison Of Qtls Detected For Grain Protein and Oil Contenmentioning
confidence: 89%
“…Since Hopkins (1899) first began to investigate selection of maize grain chemical compositions over 100 years ago, several germplasms have been developed, including Illinois high protein (IHP), Illinois low protein (ILP), Illinois high oil (IHO), and Illinois low oil (ILO) (Dudley et al, 1977;Lambert, 1992, 2004) germplasms. To date, many researchers have demonstrated the genetic mechanisms contributing to grain protein and oil contents by using statistical and molecular models (Miller and Brimhall, 1951;Dudley et al, 1977;Lambert, 1992, 2004;Goldman et al, 1993;Berke and Rocheford, 1995;Song et al, 2004;Wassom et al, 2008;Zhang et al, 2008;Li et al, 2009;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no common QTL was shared between the two populations. Wang et al (2010) used composite interval mapping and mapped 1-6 QTLs for grain oil and starch content in two populations under different environments. Wang et al (2013) used a double haploid population and identified a total of 63 QTLs for oil content.…”
Section: Introductionmentioning
confidence: 99%